Bank reserves and broad money in the global financial crisis: A quantitative evaluation - Jagjit Chadha; Luisa Corrado; Jack Meaning; Tobias Schuler (European Central Bank (ECB), 2020)
The Federal Reserve responded to the global financial crisis by initiating an unprecedented expansion of central bank money (bank reserves) once the policy rate had reached the lower bound. To capture the salient features of the crisis, we develop a model where the central bank can provide reserves on demand and also use reserves to buy government bonds. We show that the provision of reserves through either channel reduces the cost of providing loans as they act as a substitute for private sector collateral and costly monitoring activity. We illustrate this mechanism by examining the role of reserves in projecting stable growth in broad money after the financial crisis. We also run a counterfactual which suggests that, if the Federal Reserve had not provided bank reserves on such a large scale, broad money would have fallen, the economy might have experienced a deeper contraction, and the recovery would have been more protracted, taking perhaps twice as long to return to equilibrium.
Keywords: E31; E40; E51; 330; non-conventional monetary policy; quantitative easing; liquidity provision